2017
DOI: 10.17159/2519-0105/2017/v72no10a1
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of occupational health-related conditions among oral health practitioners in KwaZulu-Natal, South Africa

Abstract: introduction: Oral health practitioners may be affected by occupational health-related conditions associated with their work environment. There is a lack of relevant data on the prevalence of these conditions among dentists, dental therapists and oral hygienists in KwaZulu-Natal. aim: To describe the burden of occupational health-related conditions among oral health practitioners in KwaZulu-Natal, South Africa. Methods: This cross sectional study evaluated data obtained through a self-administered questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
8
0
2
Order By: Relevance
“…The study suggested the need for ergonomic work practice while in training to reduce the risks of MSDs later in their working careers. [15] The current study shows that students become aware of the risk of MSD through the experiences of the dental clinical staff ˃ they should heed their advice and practise the exercises shown to them by the physiotherapy students to prevent future occurrence of MSDs.…”
Section: Researchmentioning
confidence: 82%
“…The study suggested the need for ergonomic work practice while in training to reduce the risks of MSDs later in their working careers. [15] The current study shows that students become aware of the risk of MSD through the experiences of the dental clinical staff ˃ they should heed their advice and practise the exercises shown to them by the physiotherapy students to prevent future occurrence of MSDs.…”
Section: Researchmentioning
confidence: 82%
“…few that employed an analytical [43] and quasi-experimental study design [24]. The study regions included Botswana [24], Cameroon [25][26], Egypt [27], Ethiopia [10,[28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45], Ghana [46], Kenya [47], Morocco [48], Nigeria [49][50][51][52][53][54][55][56][57][58][59], South Africa [1,[60][61][62][63][64][65][66][67][68], Sudan [69], Tanzania…”
Section: Resultsmentioning
confidence: 99%
“…Moodley y cols. en 2017 en odontólogos de Sudáfrica encontró que trabajar en posturas incómodas se asoció significativamente con dolor de mano y muñeca (p = 0,015) (30) Nogueira de Sousa Silva en un estudio en Brasil en 2017 encontró que hay un aumento de TME en dentistas, mujeres, en mayores de 40 años, y en personas con comorbilidades y tabaquismo. El 38,3 presentó TME de muñeca y mano (35).…”
Section: Resultsunclassified
“…Moodley en Sudáfrica en 2011 encontró que el 22,5% de su muestra refirió dolor en las manos, 19,4%, entumecimiento en las manos y 24,4%, sensación de hormigueo en las manos mientras realizaba trabajo clínico. La eminencia tenar es un grupo de músculos ubicado en el pulgar y en la palma de la mano que permite diferentes movimientos del pulgar y este fue el sitio más trazado para el dolor (15).…”
Section: Discussionunclassified